Potential application of Batang Garing cultural values of Dayak tribe in Orangutan conservation - Farashwanti, Nida; Anisa, Risma (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: This is intended to describe the Batang Garing symbol of the Dayak Ngaju tribe in Central Kalimantan as a container for preservation. From the previous study mentioned about Batang Garing, environmental consciousness, this study attempts to identify the cultural values of the Batang Garing tribe in the life of the Dayak tribe and to seek opportunities to apply the cultural values of the Batang Garing Dayak tribe in Orangutan conservation. Methods: This study using qualitative techniques is used to measure rehabilitation and assess the contribution of rehabilitation to conservation. Findings: It can be concluded that the Batang Garing concept is in harmony with the idea of Orangutan conservation. The construction of meaning that is carried out provides space for collaboration between local values and modern values in the conservation agenda, it is hoped that this alignment will facilitate the involvement of indigenous peoples in harmony with Orangutan conservation so that they play an active role in conservation because there are several overlapping values. Conclusion: The constructs provided are expected to be useful in forming universal knowledge/which can be understood by the wider community, including policy makers, namely the Government, as well as policy observers, both academics and practitioners regarding the agenda of forest conservation. Novelty/Originality of this Study: The novelty of this study lies in its exploration of the potential application of the Dayak Tribe's Batang Garing cultural values in Orangutan conservation. This research uniquely combines indigenous wisdom with modern conservation efforts, aiming to foster community involvement and promote sustainable natural resource management.